Liberal Feminism Depicted by Wanda through the Dialogue in Dr. Strange in the Multiverse of Madness Movie - I Made Agus Wibawa Putra; I Wayan Juniartha (Austronesian: Journal of Language Science & Literature, 2023)
This research investigates the portrayal of liberal feminism in the character of the movie. The study aims to analyze the liberal feminism of Wanda, the main character in Dr. Strange in the Multiverse of Madness Movie. The data used for this research were taken from Dr. Strange in the Multiverse of Madness Movie. This study uses the descriptive qualitative method to conduct a clear and well-organized description of the problems which is identified. The theory used in this research is the theory of Miles and Huberman’s theory (1994), which involves data reduction, data display, and conclusion. The findings of the study reveal that Wanda’s character exemplifies liberal feminism through her assertion of agency and autonomy in pursuing her objectives, such as reuniting with her children in another universe, disregarding the repercussions for others. The study concludes that Wanda’s character challenges conventional stereotypes of female villains and presents a multifaceted and intricate depiction of a woman’s struggle for freedom and identity. Furthermore, the study proposes potential avenues for additional research in the field of gender and media studies.